2001
DOI: 10.1097/00045391-200105000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Contrast Media-Induced Renal Dysfunction With Prostaglandin E 1 : A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Preexisting renal impairment is an all-encompassing risk factor for radiocontrast-associated nephrotoxicity. Renal impairment appears to be associated with the inadequate production of renal prostaglandins at the critical time of radiocontrast administration and for a variable time period afterward. We prospectively studied 130 patients with chronic renal insufficiency (serum creatinine > or =1.5 mg/dL) who were undergoing radiocontrast administration. Using a double-blind, randomized, prospective technique, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 20 publications
1
45
1
3
Order By: Relevance
“…All the groups treated with prostaglandin E1, independently of given dose, experienced significantly less increase in creatinine after exposure to contrast media compared with placebo. The most pronounced effect was observed in patients that received the intermediate dose of the drug (20 ng/kg/min) [90].…”
Section: Prostaglandin E1mentioning
confidence: 98%
See 1 more Smart Citation
“…All the groups treated with prostaglandin E1, independently of given dose, experienced significantly less increase in creatinine after exposure to contrast media compared with placebo. The most pronounced effect was observed in patients that received the intermediate dose of the drug (20 ng/kg/min) [90].…”
Section: Prostaglandin E1mentioning
confidence: 98%
“…Based on the decreased levels of prostaglandins in patients with CIN, it was hypothesized that prophylactic administration of prostaglandin E1 may be beneficial in reducing CIN [90]. A double-blind, randomized, placebo-controlled study investigated the effect of intravenous administration of prostaglandin E1 in three various doses.…”
Section: Prostaglandin E1mentioning
confidence: 99%
“…28 However, only patients receiving the middle dose of alprostadil (20 ng · kg Ϫ1 · min Ϫ1 ) had significantly smaller increases in mean serum creatinine levels than the placebo group.…”
mentioning
confidence: 89%
“…Moreover, another randomized placebocontrolled study has also shown in 130 patients with renal dysfunction (baseline SCr ³1.5 mg / dL) that infusion of prostaglandin E 1 (10 -40 ng / kg per minute for 6 h) starting from 30 -60 min before RCM injection significantly diminishes the increase in SCr determined at 48 h after radiographic examination, in which the effect is most marked at a dose of 20 ng / kg per minute (95). Therefore, prostaglandin E 1 may be promising as a prophylactic agent against radiocontrast nephropathy.…”
Section: Prostaglandin Ementioning
confidence: 97%